Putin-Kim Summit : Enter the Russian Factor - Cheang, Chris (2019)
President Vladimir Putin’s meeting with North Korean leader, Kim Jong-un on 25 April 2019 in Vladivostok is not unexpected. It merely confirms that Russia has always had a role in trying to resolve the protracted issue of North Korea’s nuclear weapon development. The main purpose of this meeting is to reinforce the message that the US alone cannot influence what Pyongyang will do on denuclearisation.